Efficacy and safety of bone substitutes in lumbar spinal fusion: a systematic review and network meta-analysis of randomized controlled trials - Feng, Jiang-tao; Yang, Xiong-gang; Wang, Feng; He, Xin; Hu, Yong-cheng (European spine journal, 2020)
Purpose A variety of alternative grafts to autologous iliac crest bone (ICBG) have been developed for lumbar spondylodesis, due to frequent complications following ICBG harvest. The optimal alternative graft to ICBG, however, remains elusive till now. The purpose of this study was to compare the efficacy and safety of fusion materials in lumbar degeneration diseases and to provide a ranking spectrum of the grafts. Methods Randomized controlled trials (RCTs) comparing different bone grafts in lumbar arthrodesis were eligible for inclusion. A network meta-analysis was performed for endpoints including fusion rate and incidence of adverse events. Results Twenty-seven RCTs involving 2488 patients and 13 available interventions were included. rhBMP-2 provided the highest fusion rate, being significantly superior to that of ICBG (OR = 0.21, p < 0.001), autograft local bone (ALB) (OR = 0.18, p = 0.022), rhBMP-7 (OR = 0.15, p < 0.001), allograft (OR = 0.13, p = 0.009), and DBM + ALB (OR = 0.07, p = 0.048). The treatment efficacy of allograft could be significantly enhanced by bone marrow concentrate (BMC) supplying (OR = 0.16, p = 0.010). ICBG ranks second on the frequency of complications, which is significantly higher than that of allograft (OR = 0.14, p = 0.041) and ALB (OR = 0.14, p = 0.030). All of the other comparisons showed similar efficacy and safety profiles between groups. Conclusion Ranking spectrums of the efficacy and safety for various bone grafts were provided graphically. Though rhBMP-2 was of the highest success rate, the application should be taken with proper caution because of the widely proposed life-threatening adverse events. ALB, ALB plus synthetic ceramic materials and allograft mixed with BMC were also proved to be potentially effective alternative graft to ICBG. Graphic abstract These slides can be retrieved under Electronic Supplementary Material.